Centellograma de Pulmón - Testa, H.J.; Pecorini, Victorio; Olivari, Américo; Iotti, R.; Guerrero, M.; Chwojnik, Abraham (Comisión Nacional de Energía Atómica (CNEA), 1967)
Fil:Testa, H.J. Comisión Nacional de Energía Atómica (CNEA). República Argentina